2018
DOI: 10.1093/jcmc/zmy007
|View full text |Cite
|
Sign up to set email alerts
|

The Associations Between Online Media Use and Users’ Perceived Social Resources: A Meta-Analysis

Abstract: Conflicting findings have emerged from the large number of studies on the relationship of online media use (OMU) and users' perceived social resources (PSR). In contrast to the numerous primary studies, a comprehensive meta-analysis on the relationship between the use of different online media and PSR has been lacking to date. The findings presented are based on 342 effect sizes from 63 studies and represent data from over 35,500 individuals. The results reveal a small and positive relationship between the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 48 publications
(99 reference statements)
3
43
0
Order By: Relevance
“…One review concluded that those users who go to Facebook to promote social support and connection show lower levels of depressive symptoms [24]. Other meta-analyses have also found that social media use increases social support [36] and that online media use increases perceived social resources (r = 0.12) [16]. One way to explain such a conflict is that different outcomes were examined.…”
Section: Systematic Reviews and Meta-analyses: Social Mediamentioning
confidence: 99%
“…One review concluded that those users who go to Facebook to promote social support and connection show lower levels of depressive symptoms [24]. Other meta-analyses have also found that social media use increases social support [36] and that online media use increases perceived social resources (r = 0.12) [16]. One way to explain such a conflict is that different outcomes were examined.…”
Section: Systematic Reviews and Meta-analyses: Social Mediamentioning
confidence: 99%
“…Online vigilance is reflected in three features of users' psychology: "(1) their cognitive orientation to permanent, ubiquitous online connectedness; (2) their chronic ONLINE VIGILANCE AND AFFECTIVE WELL-BEING 6 attention to and continuous integration of online-related cues and stimuli into their thinking and feeling; and (3) their motivational disposition to prioritize options for online communication over other (offline) behavior" (Reinecke et al, 2018, p. 2 The dimensions of online vigilance can exert different influences on well-being, depending on whether the dimensions manifest themselves in thoughts and behavior that are conducive to the current task or not (Reinecke, 2018). Supporting such a view, the literature on media use and well-being suggests that goal-directed, purposeful social interactions via media can enhance social gratifications (Bayer et al, 2018;Burke & Kraut, 2016;Jung & Sundar, 2018) and contribute to well-being (Domahidi, 2018;Trepte et al, 2015). In contrast, passive use or technology use as procrastination can have negative consequences for wellbeing (Meier et al, 2016;Reinecke & Hofmann, 2016;Verduyn et al, 2015).…”
Section: Online Vigilance and Well-beingmentioning
confidence: 99%
“…Whereas monitoring has the potential to remind people of their social network (Domahidi, 2018), unprompted checks often do not serve an explicit goal; instead, monitoring regularly takes the form of non-purposeful checks (Oulasvirta et al, 2012). Monitoring can then be understood as a specific form of mindless media use, which has shown to relate negatively to well-being (Meier et al, 2016;Verduyn et al, 2015) Evidence for such a prediction comes from research showing that checking email less frequently was associated with increased well-being (Kushlev & Dunn, 2015).…”
Section: Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…At the very least, scholars need to take the imperfect reliability of self-reported media exposure into account, so that random fluctuations over time are not misinterpreted as true change in rank-order stability. Such correction mechanisms cannot only be used for primary analyses in media use and effects research (Bachl & Scharkow, 2018), but even post-hoc in meta-analyses of these effects by means of artifact correction (Domahidi, 2018). Moreover, the high stability of media use provides all the more reason to move on from mere media or outlet-as-cause studies to more elaborate linkage studies (Scharkow & Bachl, 2017).…”
Section: Discussionmentioning
confidence: 99%